KADAR TANIN, KALSIUM DAN FOSFOR SILASE KULIT PISANG KEPOK (Musa paradisiaca) DENGAN ADITIF GULA AIR - Theresia Nur Indah Koni; Yulianus Ugu; Helda Helda (Politeknik Pertanian Negeri Kupang, 2022)
Banana peel is a potential alternative feed source, but its use is limited by its tannin content. Tannins bind proteins, and minerals and reduce protein digestibility. The experiment aimed to evaluate the effect of palmyra sugar liquid (PSL) on tannin, calcium, and phosphorus levels of banana peel silage. This study used a completely randomized design with 4 treatments and 5 replications. The treatments were GA0: banana peel without PSL, GA2: banana peel + 2% PSL, GA4: banana peel + 4% PSL, and GA6: banana peel + 6% PSL. A mixture of banana peels and PSL was put into a plastic jar while compacted. Then tightly closed and fermented for 21 days. Variables observed were the tannin, calcium, and phosphorus content of banana peel silage. The results showed that the PSL level had a very significant effect (P<0.01) on the tannin, calcium, and phosphorus content of kepok banana peel silage. The use of 4% water sugar can reduce tannin levels and has the highest levels of calcium and phosphorus of kepok banana peel silage.Key Words: Banana peel, Calcium, Fermentation, Phosphorus, Tannin